Australia and Stateless Palestinians - Taylor, Savitri (Refuge: Canada’s Journal on Refugees, 2006)
This article considers Australia’s treatment of stateless Palestinian asylum seekers and discusses whether that treatment discharges Australia’s legal and/or moral obligations towards the individuals in question. The conclusion drawn is that it does not.